Scalable nanoprecipitation of niclosamide and in vivo demonstration of long-acting delivery after intramuscular injection. Issue 13 (25th March 2021) - Hobson, James J.; Savage, Alison C.; Dwyer, Andrew B.; Unsworth, Catherine; Massam, Jonathan; Arshad, Usman; Pertinez, Henry; Box, Helen; Tatham, Lee; Rajoli, Rajith K. R.; Neary, Megan; Sharp, Joanne; et al.
Abstract : Controlling COVID-19 requires therapy and continued vaccination. Long-acting therapeutics offer options for test-and-cure strategies and overcome poor therapy adherence. Extended  in vivo  niclosamide exposure is demonstrated here as such a candidate. Abstract : The control of COVID-19 across the world requires the formation of a range of interventions including vaccines to elicit an immune response and immunomodulatory or antiviral therapeutics. Here, we demonstrate the nanoparticle formulation of a highly insoluble drug compound, niclosamide, with known anti SARS-CoV-2 activity as a cheap and scalable long-acting injectable antiviral candidate.